EXPERIENCES OF THE CZECH TOXICOLOGICAL INFORMATION CENTRE WITH ETHYLENE GLYCOL POISONING - Krenova, Martina; Pelclova, Daniela; Navratil, Tomas; Merta, Miroslav (Biomedical papers, 2005)
The objective was to evaluate the severity of ethylene glycol (EG) intoxications in a 3-year retrospective study of the calls to the Toxicological Information Centre (TIC). Data about clinical course of patients with EG poisoning reported to the TIC in the years 2000-2002 were analysed. They were completed by the data from discharge records from the hospitals and by toxicological analyses. The χ-square test, Student's t-test, Fisher's test and the calculation of linear correlation coefficient were used for statistical analysis. The significance level was set at 0.05. TIC received total 188 calls concerning EG, from which 33 discharge reports were gained. There were 30 males (age 5-74 years) and 3 females (age 10-54 years). The patients ingested 252 ml on average (30-1000 ml); lethal dose (100 ml) was exceeded in 14 patients. Mean time interval from ingestion to admission was 3 hours (3-24 hours), mean length of hospitalisation 6 days (1-76 days). Fourteen patients developed metabolic acidosis, nine unconsciousness, thirteen signs of nephrotoxicity and nine signs of hepatotoxicity. Three patients died. Antidote ethanol was given in 30 patients. Other treatment included haemodialysis (20 cases) and B vitamins (23 cases). Ingested dose and the time interval between ingestion and admission correlated with severity of kidney damage. These data confirm that EG poisoning could seriously threaten the life. Renal parameters were abnormal in 30 % of patients who were discharged from the hospital. Those patients will be followed to evaluate the reversibility of EG toxic kidney damage.
Keywords: Ethylene glycol/Intoxication/Haemodialysis/Acute renal failure/Nephrotoxicity/Czech Republic